Comparative Analysis of Conventional and Thin Prep Papanicolaou Test. Technical and Economic Aspects - Mary Giachnaki; Elena Athanasiadi; Abraham Pouliakis; Aris Spathis; Christine Kottaridi; Evangelia Aga; Maria Papaefthimiou; Panagiota Mentzelopoulou; Helen Spathi; Petros Karakitsos (Annals of Cytology and Pathology - Peertechz Publications, 2016)
Background: Cervical cancer is the fourth most common cancer and a leading cause of death due to cancer, in female population worldwide. Prevention is performed via the Papanicolaou test. Since 90ies, this test can be performed via two methods: the conventional method, where cells are layered on a glass slide, immediately after their extraction and Liquid Based Cytology (LBC), where cells are stored in a vial containing a special liquid. Purpose of the study: To evaluate the performance of conventional and LBC Papanicolaou test in technical level, by assessing the diagnostic performance as well as the disadvantages of each method, and to carry out an economic evaluation via cost effectiveness analysis between the two methods. For this purpose we analyzed the results of 23,604 conventional tests and the equal number of LBC tests. Results: LBC had better performance than conventional Papanicolaou test. The percentage of inadequate samples was reduced by 37.8%, the percentage of ambiguous examination results was reduced by 52.6%. LBC additionally detects significantly higher number of squamous intraepithelial neoplasias (27.7% improvement on LSIL and 19.1% on HSIL). In terms of cost effectiveness, the analysis showed that the cost for every gained life year when applying LBC is less that 50€, significantly lower than the amount of 50,000$ proposed by insurance organizations.Conclusions: LBC Papanicolaou test presents significantly better performance characteristics than the conventional test, it also enables the application of modern ancillary examinations relevant to the HPV lifecycle and moreover, the associated extra cost for the gained life years is significantly low.